Surficial geology and geomorphology of Greg crater, Promethei Terra, Mars. Issue 2 (9th December 2020) - Tsibulskaya, V.; Hepburn, A.J.; Hubbard, B.; Holt, T.
ABSTRACT: Greg crater, located in Promethei Terra, Mars is a ∼66 km diameter impact crater. The crater has been widely studied, both in terms of its overall geomorphological evolution and, more specifically, its ice-rich landforms. One category of these, glacier-like forms, appears to be closely analogous to valley glaciers on Earth. However, Greg crater hosts many other features, the origins and inter-relationships between which are of continuing interest. Here, the surficial geology and geomorphology of Greg crater is presented, identifying seven distinct groups of terrain types or landforms. We identify and classify these based on their physical appearance, guided by published descriptions and interpretations to illustrate the wide variety of landforms and terrain types that, elsewhere, could be used to investigate landscape development.